Proceedings of the 4th Progressive and Fun Education International Conference (PFEIC 2019) 2019
DOI: 10.2991/pfeic-19.2019.15
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Anatomical Characteristic Kinship of Faloak Plant (Sterculia quadrifida R.Br) as Learning Source for Morphology and Anatomy of Plant Course Based on Local Natural Resources

Abstract: This study aims to determine the morphological and anatomical characteristic kinship of faloak plant (Sterculia quadrifida R.Br) growing in Kupang Regency as learning source for morphology and anatomy of plant course based on local natural resources. The study was conducted at the Laboratory of Biology Education Study Program, Kupang Muhammadiyah University from March to May 2019. This study used a qualitative descriptive approach with cluster analysis method. To see the kinship of the plant, this study used U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In this case, a module integrating local-based materials such as the Faloak plant can trigger students to learn and enhance their motivation (Tazhitova et al, 2022). The integration of Faloak plants as learning material in this research is because of their suitability as learning material in science, which has already been confirmed by Lestari (2019). She suggests the appropriateness of the Faloak plant as learning material for morphology and anatomy subjects.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…In this case, a module integrating local-based materials such as the Faloak plant can trigger students to learn and enhance their motivation (Tazhitova et al, 2022). The integration of Faloak plants as learning material in this research is because of their suitability as learning material in science, which has already been confirmed by Lestari (2019). She suggests the appropriateness of the Faloak plant as learning material for morphology and anatomy subjects.…”
Section: Introductionmentioning
confidence: 56%
“…They also report the low level of students' critical thinking skills. Lestari et al (2019) observed junior high school students in Kupang, Indonesia. They found that the students needed more ability to argue and could not interpret issues in the learning process, indicating their lack of critical thinking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…which is known as faloak, belonging to the family Sterculiaceae, widely distributed in Indonesia, especially in Timor, Sumba, Alor, and Flores Island [6]. Conventionally, in Indonesia, especially East Nusa Tenggara, the bark of this plant is used to treat liver diseases, gastroenteritis and as stamina booster [7], rheumatism, and malaria [8]. The ethanolic extract of S. quadrifida bark had been reported to have cytotoxicity activity on hepatocyte cell line Huh7 and inhibition activity to HCV JFH1 replication [9], antidiabetic [10], and immunomodulatory [11].…”
Section: Introductionmentioning
confidence: 99%